2022
DOI: 10.1111/aor.14415
|View full text |Cite
|
Sign up to set email alerts
|

The effect of source animal age, decellularization protocol, and sterilization method on bovine acellular dermal matrix as a scaffold for wound healing and skin regeneration

Abstract: Background: Healing the full-thickness skin wounds has remained a challenge.One of the most frequently used grafts for skin regeneration is xenogeneic acellular dermal matrices (ADMs), including bovine ADMs. This study investigated the effect of the source animal age, enzymatic versus non-enzymatic decellularization protocols, and gamma irradiation versus ethylene oxide (EO) sterilization on the scaffold. Methods: ADMs were prepared using the dermises of fetal bovine or calf skins.All groups were decellularize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…These results indicate that the decellularization method was effective for the preparation of FADM with favorable properties for downstream experiments. In addition, we previously reported that this decellularization method provided a matrix with favorable mechanical and thermal properties [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results indicate that the decellularization method was effective for the preparation of FADM with favorable properties for downstream experiments. In addition, we previously reported that this decellularization method provided a matrix with favorable mechanical and thermal properties [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that the use of xenograft ADM, in combination with WJ-MSCs, not only significantly improved wound healing but no inflammation or immunological reactions were observed, and no specific growth factors were used. In our previous work, we also showed that the use of FADM induced neovascularization and skin regeneration while no inflammation was observed [ 25 ]. Here, we also showed that FADM-WJ-MSCs express a higher level of antigenic factors when cultured in vitro for 7 days.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this regard, protecting the wound from dehydration, supplying oxygen, and inhibiting infections are the primary roles of bioengineered skin substitutes. [12][13][14][15][16][17][18] Human ASCs are one of the main sources of stem cells for TE applications as they possess great benefits, including excellent proliferation ability, simplicity of isolation from adipose tissue, and hypoimmunogenic property. [19][20][21] More importantly, they secrete different growth factors (GFs) as well as anti-inflammatory cytokines that can promote neo-vascularization and re-epithelialization.…”
mentioning
confidence: 99%